Pengaruh Diet dan Indeks Masa Tubuh Terhadap Derajat Keparahan Akne Pada Mahasiswa/I Semester 2 (Angkatan 2024) dan Semester 4 (Angkatan 2023) Fakultas Kedokteran Universitas Prima Indonesia - Sinulingga, Honey; Sartika, Dewi; Nasution, Masdalena (Syntax Literate, 2025)
Research Objective: To find out whether there is an effect of Body Mass Index (BMI) and Diet Pattern on the severity of acne vulgaris. Research Method: This type of research is observational analysis with a cross sectional approach. This research will be conducted in June 2025 at Universitas Prima Indonesia. The subjects of this study are students of the 2023 and 2024 batches who meet the inclusion and exclusion criteria set by the researcher. Sampling was carried out by stratified random sampling with a total of 97 samples. All samples filled out questionnaires to obtain data on the severity of acne in each sample, diet patterns each week, and BMI values for each sample. The data were then analyzed using chi-square with a significant level of p<0.05. Study results: The results showed that there was a significant influence between diet pattern and the severity of acne vulgaris (p=0.011) and between body mass index (BMI) and the severity of acne vulgaris (p=0.047). Respondents with a high diet pattern and overweight or obese BMI were more at risk of moderate to severe acne compared to normal renal and BMI diets. Conclusions: There is a significant influence between high dietary patterns and overweight or obesity body mass index on the severity of acne vulgaris. The higher the BMI and the worse a person's diet pattern, the more severe the severity of acne vulgaris experienced.